Dominação, incesto e liberdade : Paula e o narrador em Pedro e Paula, de Helder Macedo - Lopes, Giovana dos Santos (2009)
Current research focuses on the novel Pedro e Paula (1998). The novel is inscribed by a Portuguese society which suffered dictatorship, war, revolution and a post-revolution period. Above-mentioned marks are represented in the characters that author Helder Macedo employs to demonstrate the construction of mirroring in metaphors portrayed in Portugal and in Africa. Fiction and reality are thus mixed up within the entire context, between suggestions and hypotheses offered by the narrator. The latter is very similar to the author and may mislead the less attentive reader. The narrator, also called Helder Macedo, positing as the fictional writer of a hypothetic novel, makes his characters track their way through which they may exalt his preferred Paula. Paula is a perfection type that the narrator confesses to construct according to this aspect by using an alluring discourse as one of the resources to reveal her character. Based on these traits, the main aim of our research, Bakhtin's theoretical concepts are brought forth in his studies of voices in the novel and the manner they become present according to discourse context in the literary and social stance. Through analyses of voices in the social field, Bourdieu's investigation verifies the ideology of male dominance in the characters' discourse and what this fact implies in Paula's character traits. Within a plethora of voices and ideologies, the theories of Kristeva and Cixous contribute towards the development for male authorship, or rather, that the male author may represent the female character as much as the female author. The study of the construction of the character Paula and the implications involved are undertaken.